Svoboda veroizpovedi kot temeljna človekova pravica v slovenski tranziciji - Stres, Anton (Bogoslovni vestnik, 2004)
During the period of communist totalitarianism in Yugoslavia religion was defined in the constitution as "a private matter of any individual", which meant that it was completely excluded from the area of public life and activity. By democratiyation these limitations were abolished, but the attitude towards religion and the Church that was reigning for over one half of the century created stereotypes and habits in the mentality that cannot be easily overcome. The text of the Constitution of the Republic of Slovenia does not really comprise a basis for a particularly restrictive and laicist attitude to religion and the Church, yet the mentality of the people, some laws and the general political orientation make Slovenia one of the European countries with the strongest laicism and with the most hostile attitude of the state towards religion. This can very clearly be seen in the area of education where the legislation explicitly prohibits any denominational activity in (public) schools, whereby Slovenia differs from the general co-operative relationship between the state and the Church, which is the most frequent model in Europe.
Keywords: communism; creed; Človekove pravice; freedom of religion; human rights; komunizem; laicism; laicizem; liberalism; liberalizem; religious freedom; Veroizpoved; verska svoboda